Towards Sustainable C−H Functionalization Reactions: The Emerging Role of Bio‐Based Reaction Media. Issue 51 (20th June 2018) - Santoro, Stefano; Marrocchi, Assunta; Lanari, Daniela; Ackermann, Lutz; Vaccaro, Luigi
Abstract: In the last decade, transition‐metal catalyzed C−H functionalization reactions have progressed enormously, becoming a useful tool in organic synthesis and a practical alternative to well‐established methodologies. Very recently, research efforts have also been devoted to developing more sustainable C−H functionalization protocols, in order to increase their applicability. One of the most promising approaches in this sense is represented by the substitution of common reaction media with bio‐based solvents. In the present contribution a general perspective on the benefits of this approach is given, followed by key literature examples. Abstract : Greener C−H functionalizations : The use of bio‐based chemicals as alternative reaction media allows for reducing waste‐generation, thus increasing the applicability of this rapidly‐growing synthetic tool.